Ta'lim Al-Mufradat Bi Tariqah As-Sam'iyah Al-Lugawiyah Wa Tatbiquha Fi Tarqiyah Maharah Al-Kalam Li Tullab Madrasah Hifd Al-Qur'an bi Medan - Triandani, Mirsa; Salamuddin, Salamuddin (LPPM Universitas KH.A. Wahab Hasbullah, 2025)
This study aims to analyze the application of audiolingual method in improving maharah kalam (speaking skills) for students of class VII 3 MTs Yayasan Islamic Center Medan. This audiolingual method is based on the theory of behaviorism, which is used with a focus on listening exercises, imitating, and repeating Arabic sentence patterns to improve pronunciation, sentence structure, and student confidence in speaking. This research is a field research with a qualitative descriptive approach, with data collection techniques through observation, interviews, and documentation. The results showed that the application of the audiolingual method was effective in improving the ability of students in class VII 3 MTs Yayasan Islamic Center Medan in terms of pronunciation of hijaiyah letters, pronunciation of words, and the ability to express intentions with appropriate sentences. Supporting factors consist of clear teacher pronunciation examples, intensive practice, a pleasant learning atmosphere, and motivation. The obstacles found include students' limited vocabulary, difficulty understanding the meaning of words, and the lack of focus of some students. With consistent practice and a structured method, audiolingual method can be an effective alternative to develop students' maharah kalam in Arabic language learning.